Strategi Penataan Organisasi Skadron Penerbad Dalam Rangka Mendukung Pertahanan Ibu Kota Nusantara (IKN) - Hidayat, Syarif; Munawaroh, Siti; Tjahyono (Bahtera Inovasi, 2024)
The relocation of the capital city from Jakarta to East Kalimantan shifts the Centre of Gravity (COG) to various potential threats in northern Indonesia. This relocation introduces a new dimension in the country's defense and security strategy. Consequently, the nation's defense aspects, represented by the Army Aviation (Penerbad), must prepare and restructure their organization to support this defense effort. The Army Aviation unit stationed in the Nusantara Capital, specifically Squadron-13/Serbu, faces challenges in personnel, material, and facility aspects. Therefore, this study aims to determine organizational restructuring strategies for Squadron-13/Serbu through the perspectives of personnel, material, and facilities. This research utilizes a qualitative research design with a descriptive-explorative approach. The findings indicate that, for the personnel aspect, Squadron-13/Serbu can optimize eight existing strategies. In terms of the material aspect, nine organizational restructuring strategies can be optimized. Meanwhile, for the facilities aspect, Squadron-13/Serbu can enhance process flow reorganization, organizational innovation, resource management, as well as flexibility and adaptability. This study is expected to contribute to the academic literature concerning military organization and defense organizational restructuring.